S.Wahyuni Analisis Program Pembelajaran Tatap Muka (PTM) Terbatas pada Siswa Sekolah Dasar - Wahyuni, Sri; H.M Arief; Hisbullah (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The spread of the COVID-19 virus in 2020 has spread very quickly so far it has had a very large impact, especially in the field of education.This study uses a qualitative descriptive research type. Data collection techniques were carried out by means of observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, condensing data, presenting data and verifying or drawing conclusions. The subjects of this study were the principal and 3 homeroom teachers in class V SDN 1 Lalebbata.The results of the study indicate that teacher planning must prepare teacher administration according to the conditions experienced such as educational calendars, promissory notes, prota, syllabus, lesson plans, absent books, KKM, grade lists, package books, teaching materials, and class rules. For the implementation of learning, each class divides its students into two parts, there is the morning shift at 07.30-09.00 and for the afternoon shift at 09.30-11.00. The teacher's activities are limited so that the teacher only conveys important points of the material the teacher also does not do several learning steps in the classroom, namely the teacher does not convey the allocation of learning time, the teacher does not provide interesting learning media and the teacher does not apply learning strategies in groups. Likewise with the evaluation of learning the teacher does daily tests and daily tasks as usual and the learning outcomes of students also improved when compared to learning done at home.As for the limited face to face learning program, the reserarcher should have intiated 6 new steps, namely 1) Teachers deliver material by using learning methods that can attract students’ learning intersest, 2) Teachers provide student centered learning materials, 3) Teachers evaluate understanding students, 4) The teabhers desingns an assessment rubric, 5) The teacher acts as a motivation, 6) The teacher acts as a provide of learning experiences